1992
DOI: 10.1176/ajp.149.12.1687
|View full text |Cite
|
Sign up to set email alerts
|

Combined pharmacotherapy and psychotherapy in the acute and continuation treatment of elderly patients with recurrent major depression: a preliminary report

Abstract: Use of nortriptyline plus interpersonal psychotherapy for 9.1 weeks (median) of acute and 16 weeks of continuation therapy appears to be associated with good response and relatively low attrition but about a 25% chance of relapse during double-blind discontinuation of nortriptyline. These data require confirmation in a controlled clinical trial of acute and continuation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Data for the current study include 711 depressed patients drawn from 6 clinical trials conducted at the University of Pittsburgh between 1982 and 2001: Maintenance Therapies in Recurrent Depression, 19 Maintenance Therapies in Late-Life Depression, 20 Psychobiology of Recovery from Depression, 21 Nocturnal Penile Tumescence in Depression Study, 22 Social Zeitgebers in Depression, 23 and Maintenance Psychotherapy in Recurrent Depression. 24 Detailed methods and main hypotheses for each of these studies have been published previously.…”
Section: Methodsmentioning
confidence: 99%
“…Data for the current study include 711 depressed patients drawn from 6 clinical trials conducted at the University of Pittsburgh between 1982 and 2001: Maintenance Therapies in Recurrent Depression, 19 Maintenance Therapies in Late-Life Depression, 20 Psychobiology of Recovery from Depression, 21 Nocturnal Penile Tumescence in Depression Study, 22 Social Zeitgebers in Depression, 23 and Maintenance Psychotherapy in Recurrent Depression. 24 Detailed methods and main hypotheses for each of these studies have been published previously.…”
Section: Methodsmentioning
confidence: 99%
“…One Nevada HMO found that patients on SSRIs, 80% of whom had never seen a psychiatrist, had been taking the antidepressants for an average of 3 years (over half for more than 9 months) without being withdrawn [133]. In studies advocating long-term maintenance on antidepressants for relapsers [134, 135, 136, 137, 138, 139], recovery from depression has typically been defined in terms of symptomatic remission for a specified period of time [140]. For a patient to be considered recovered in these studies, there is no requirement that treatment be discontinued, even though the concept of recovery implies the possibility that treatment can be discontinued [114].…”
Section: Belief No 4: Antidepressants Are More Effective Than Psychomentioning
confidence: 99%
“…With regard to treatment, older depressed patients may be undertreated compared with younger adults [13]. Yet, over 80% of elderly depressed outpatients without significant comorbid medical illness or dementia who are optimally treated may recover and remain well during follow-up [9, 14]. …”
Section: Introductionmentioning
confidence: 99%